Vaping Among Adolescents in Tuva: Prevalence, Risk Factors, and Associations with Psychosomatic Spectrum Disorders - Evert, Lidiya S. (The New Research of Tuva, 2025)
This article presents the findings of a study on the prevalence and characteristics of electronic cigarette (EC) use among adolescents residing in the Republic of Tuva. The analysis was based on data obtained through online testing of random samples of adolescents aged 15–18 (total n=619), using a screening questionnaire administered via Google Forms, a vaping survey, and the psychometric questionnaire SCL-90-R. The predictive value of the indicators as potential risk factors for psychosomatic spectrum disorders (PSD) was assessed using odds ratios (OR) and their confidence intervals (CI). The study found that the prevalence of vaping among adolescents in Tuva is 18.6%, with similar rates between males and females (9.4% and 9.2%, respectively), and higher levels observed in the older age group (17–18 years, 12.6%) compared to the younger group (15–16 years, 6.0%). Key risk factors associated with increased susceptibility to EC use among adolescents included low awareness among adolescent vapers regarding the adverse effects of ECs on bodily health, beliefs about the safety of ECs, and the perception of ECs as harmless alternatives to conventional cigarettes. A wide range of risk factors for PSD and disturbances in psycho-emotional functioning associated with EC use were identified. Vaping emerged as a highly informative risk factor for impairments in psycho-emotional health, including somatization, obsessive-compulsive symptoms, interpersonal sensitivity, depression, anxiety, hostility, and psychoticism. The study results highlight the urgent need for a comprehensive approach to addressing this issue, including improving awareness about electronic nicotine delivery systems, actively identifying vaping behavior among Tuvan adolescents, and providing effective interventions for associated health disturbances.